Development Of Android Application-Based Thematic Learning Media - Muhammad Sururuddin; Ratna Indriana (IJE : Interdisciplinary Journal of Education, 2023)
This study aims to develop thematic learning media based on Android applications used the Borg and Gall development research design which consists of is simplified into 7 stages, namely: 1) potential and problems, 2) gathering information, 3) product design, 4) design validation, 5) design improvement, 6) product trial, 7) product revision. This research was conducted for class III students of MI NW 1 Kelayu. Data collected instruments include validation sheets, student response questionnaires, and teacher response questionnaires. Technical analysis of the data used in this study is a five-scale formula for validation tests, student response questionnaires, and teacher response. The results of this study indicate that the results of the media expert validation test are categorized as "very good" with a range of X scores > 92.28-110, and the total score was 102 and an average of 4.6. The results of the material expert validation test were in the "very good" category because they were in the X score range >37.8-45 with a total score of 39 and an average of 4.3. While the results of student responses that have been carried out using student response questionnaires from 16 respondents were in the "very good" category with a total score of 44.8 and were in the X score range > 41.88-50, which means the thematic learning media based on android applications developed suitable for used in the learning process.